1988
DOI: 10.1021/jf00081a064
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-linked immunosorbent assay employing monoclonal antibody specific for deoxynivalenol (vomitoxin) and several analogs

Abstract: A monoclonal antibody was prepared against deoxynivalenol (DON, vomitoxin), a trichothecene mycotoxin occurring in grain contaminated with Gibberella zeae (anamorph = Fusarium graminearum), and incorporated into competitive direct and indirect enzyme-linked immunosorbent assays (ELISAs). DON antibodies were secreted by hybridomas derived from mice inoculated with DON conjugated to bovine serum albumin. Conjugation of DON to carrier proteins was facilitated by conversion of DON to 3-O-hemisuccinyl-DON after pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
1
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 21 publications
0
64
1
1
Order By: Relevance
“…Enzyme-linked immunosorbent assay (ELISA) [11], lateral-flow immunoassay [12], and radioimmunoassay [13] are all effective methods for mycotoxin detection. In addition to these immunoassays, surface plasmon resonance (SPR) has recently been applied to mycotoxin analysis [14].…”
Section: Introductionmentioning
confidence: 99%
“…Enzyme-linked immunosorbent assay (ELISA) [11], lateral-flow immunoassay [12], and radioimmunoassay [13] are all effective methods for mycotoxin detection. In addition to these immunoassays, surface plasmon resonance (SPR) has recently been applied to mycotoxin analysis [14].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers found that proper orientation of DON on the carrier protein was critical to antibody production. Since DON cannot be directly conjugated to carrier proteins, chemical groups capable of covalent linkage to protein must be introduced onto the molecule (Casale et al, 1988). In this paper, DON-CBSA conjugate was used as the immunogen.…”
Section: Monoclonal Antibody Preparation and Characterizationmentioning
confidence: 99%
“…But they are thought to be unsuitable for measuring many samples within a short time. In addition, some researchers have established enzyme-linked immunosorbent assay (ELISA) for DON (Casale, Pestka, & Hart, 1988;Sinha, Savard, & Lau, 1995), and it is also unsuitable for on-site detection.…”
Section: Introductionmentioning
confidence: 99%
“…So far, all the previously reported DON-MAbs were selected by homologous screening and most of them displayed much higher affinity either to 3-acetyl-DON (3-ADON) (Baumgartner et al, 2010;Casale et al, 1988;Maragos and McCormick, 2000;Tangni et al, 2010) or to 15-acetyl-DON (15-ADON) (Dos Santos et al, 2011;Maragos et al, 2011;Nicol et al, 1993;Sinha et al, 1995;Xu et al, 2010), the two derivatives that often co-occur with DON. Thus, the relevant immunoassays could only be used to screen for DON/3-ADON or DON/15-ADON, not three of them simultaneously.…”
Section: Introductionmentioning
confidence: 99%